Eco colour : botanical dyes for beautiful textiles - Flint, India (Loveland : Interweave, 2008)
"Dying with plants is a kind of botanical alchemy, and in Eco Colour, artistic dyer and colorist India Flint teaches you how to cull and use leaves, roots, and flowers to color your cloth and yarn. From whole-dyed cloth and applied color to prints and layered dye techniques, India describes only ecologically sustainable plant-dye methods using renewable resources and takes the path of doing the least possible harm to the dyer, the end user of the object, and the environment. Recipes include a number of entirely new processes developed by India herself, as well as guidelines for plant collection, directions for distillation of nontoxic mordants, and methodologies for applying plant dyes. Eco Colour inspires both the novice home dyer and textile professional seeking to extend their skills using India's successful methods for achieving ecologically friendly, stunning color."--Publisher description.
Before you begin. 'Natural' dyes - a context ; Collecting plants - a protocol -- The workspace: harvesting, health and safety. Equipment and a place to work ; Harvesting and storing plants for dyeing -- Natural dyestuffs. Some traditional dye materials -- Preparing, processing and applying dyes. Preparing to dye ; Mordants ; Processing plant dyes -- Some special dyeplant groups. Eucalyptus dyes ; Beyond the eucalyptus ; Ice-flower dyes ; Fruits and berries -- Special effects. Cold-bundled eco-prints ; Non-eucalyptus eco-prints using hot-bundling ; Hapa-zome - beating colour into cloth.
Bibliografische referenties ; index
Keywords: Dye plants; Dyes and dyeing -- Textile fibers; Dyes and dyeing, Domestic